Preoccupied with the self: towards self-responsible, enterprising, flexible and self-centred subjectivity in education. Issue 1 (2nd January 2016) - Brunila, Kristiina; Siivonen, Päivi
Abstract : In the neoliberal order, the ideal self is self-responsible, enterprising, flexible and self-centred. Regarding this ideal we argue that the rise of therapisation in society, and in education, particularly, links both the therapeutic and enterprising discourses. The article examines how these discourses jointly produce and legitimate the ideal, and thus, the preoccupied subjectivity of the neoliberal order. As a discursive form of power therapisation is observed here to work by directing students to focus on their inner selves – including their problems, vulnerabilities, dependencies as well as reactions to life events – in a therapeutic mode. And it does not stop there. Therapeutic discourses offer a seemingly empowering and flexible subjectivity, which is central in enterprising discourses. At the same time, however, selfhood tends to diminish to the extent that we argue for a need to understand more about the subjectivities that emerge from the alliance between therapeutic and enterprising discourses.